2018
DOI: 10.3892/ijo.2018.4271
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin inhibits the activation of the mTOR pathway, resulting in autophagic cell death and decreased ER expression in ER-positive human breast cancer cells

Abstract: Arctigenin, a member of the Asteraceae family, is a biologically active lignan that is consumed worldwide due to its several health benefits. However, its use may pose a problem for patients with estrogen receptor (ER)α-positive breast cancer, since studies have shown that arctigenin is a phytoestrogen that exerts a proliferative effect by binding to the ER. Thus, in this study, we examined the effect of arctigenin on ERα-positive MCF-7 human breast cancer cells to determine whether the consumption of arctigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Arctigenin, one component of dietary vegetables (greater burdock) in Asia, especially China, Korea and Japan, has therapeutic effect on anti‐influenza, antioxidant, antiviral, anti‐inflammatory, neuronal protection and anticancer treatment. However, no previous studies have clarified its effects and underlying mechanisms on the treatment of OA. Thus, the current study sheds new light on the potential protective role in OA both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arctigenin, one component of dietary vegetables (greater burdock) in Asia, especially China, Korea and Japan, has therapeutic effect on anti‐influenza, antioxidant, antiviral, anti‐inflammatory, neuronal protection and anticancer treatment. However, no previous studies have clarified its effects and underlying mechanisms on the treatment of OA. Thus, the current study sheds new light on the potential protective role in OA both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Arctigenin (ATG), a phenylpropanoid dibenzylbutyrolactone lignan, is pulled from the seed of Arctium lappa L ( A lappa ), which is commonly known as greater burdock, a kind of edibles worldwide . More and more researchers have subscribed to the view that ATG possesses immeasurable pharmacological value, including antioxidant, neuronal protection, antiviral and anti‐inflammatory effects . The anti‐inflammatory effect has been confirmed on LPS‐induced inflammation models in RAW264.7 cells or human U937 macrophage cells by means of restraining NF‐κB, JAK‐STAT and MAPK pathway .…”
Section: Introductionmentioning
confidence: 99%
“…The anti-cancer activity of ATG has been reported to due to the induction of apoptosis mediated by mitochondrial disruption and cell cycle arrest in breast, lung, bladder, gastric, hepatic, and colon cancer cells [14][15][16][17][18]. In a recent study, we showed ATG suppressed metastatic potential and induced autophagic cell death by inhibiting estrogen receptor (ER) expression in MCF-7 human breast cancer cells [19,20]. Also, Wang et al reported human non-small cell lung cancer (NSCLC) cells treated with ATG exhibited greater chemosensitivity to cisplatin-induced apoptotic cell death mediated by the down-regulation of survivin [21].…”
Section: Introductionmentioning
confidence: 99%
“…Arctigenin exhibits distinct biological activities, including antiviral (Dias et al, ; Hayashi, Narutaki, Nagaoka, Hayashi, & Uesato, ), neuroprotection (Song et al, ; Zhu et al, ), antidiabetic (Huang et al, ; Zeng et al, ), and anticancer (Chen et al, ; Huang et al, ; Hsieh et al, ; Jeong, Hong, Jeong, & Koo, ; Lei, Gan, Zhao, Yu, & Hu, ; Li, Liang, Tian, & Hu, ; Maimaitili et al, ; Wang, Solorzano, et al, ; Susanti et al, ). A growing body of literature documents that arctigenin can induce cell cycle arrests, apoptosis, autophagy, and antimetastasis in multiple types of cancer cells, including prostate (Wang, Solorzano, et al, ), breast (Feng et al, ; Hsieh et al, ; Lou, Zhu, Zhao, Zhu, & Zhao, ; Maxwell, Lee, Kim, & Nam, ), lung (Lei et al, ), liver (Susanti et al, ), gastric (Jeong et al, ), ovarian (Huang et al, ), colon cancer (Li et al, ), and glioma (Maimaitili et al, ). The anticancer efficacy of arctigenin in vivo also has been reported in human cancer cell xenograft model in athymic nude mice (Feng et al, ; Wang, Solorzano, et al, ).…”
Section: Introductionmentioning
confidence: 99%